Learning the basics of computer hardware, part 1: General components. - Robinson PS (Journal of the American Academy of Physician Assistants, 1994)
As computers become more of a part of our professional and personal lives, PAs will need to be familiar with the basic units that make up a computer system and how they work. Also, PAs must stay abreast of developments in the computer industry to determine how an when a computer system will need to be updated. Because computers have been designed to be modular, they are expandable as newer technologies emerge. PAs may find it easier to make decisions on puchasing a personal computer once they are more familiar with its hardware, such as monitors, keyboards, mouse and trackball pointing devices, cases and power supplies, central processing units, motherboards, memory and storage, hard drives, and video display adaptors. However, acquiring knowledge of hardware is just the first step in learning about personal computers.